2018
DOI: 10.1093/jeea/jvy023
|View full text |Cite
|
Sign up to set email alerts
|

Crowdfunding, Efficiency, and Inequality

Abstract: Standard-Nutzungsbedingungen:Die Dokumente auf EconStor dürfen zu eigenen wissenschaftlichen Zwecken und zum Privatgebrauch gespeichert und kopiert werden.Sie dürfen die Dokumente nicht für öffentliche oder kommerzielle Zwecke vervielfältigen, öffentlich ausstellen, öffentlich zugänglich machen, vertreiben oder anderweitig nutzen.Sofern die Verfasser die Dokumente unter Open-Content-Lizenzen (insbesondere CC-Lizenzen) zur Verfügung gestellt haben sollten, gelten abweichend von diesen Nutzungsbedingungen die in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(9 citation statements)
references
References 31 publications
0
9
0
Order By: Relevance
“…Crowd participation in an ECF campaign can provide important insights into the quality and ultimate success of the startup (Ahlers et al, ; Hornuf & Schwienbacher, ). Grüner and Siemroth () develop a theoretical model where consumers have private consumption preferences and might invest in an ECF campaign. Based on their preferences, future consumers become investors, identify worthwhile ECF campaigns, and fund the firms they like.…”
Section: Theory and Hypothesesmentioning
confidence: 99%
“…Crowd participation in an ECF campaign can provide important insights into the quality and ultimate success of the startup (Ahlers et al, ; Hornuf & Schwienbacher, ). Grüner and Siemroth () develop a theoretical model where consumers have private consumption preferences and might invest in an ECF campaign. Based on their preferences, future consumers become investors, identify worthwhile ECF campaigns, and fund the firms they like.…”
Section: Theory and Hypothesesmentioning
confidence: 99%
“…Lee and Persson (2016) also highlights the importance of informal financing and donations in a more classic investment setup. Other recent equity crowdfunding work include Grüner and Siemroth (2017), Abrams (2017), and Li (2017). Equity crowdfunding is closer to an investment game rather than a contribution game.…”
Section: Literature On Crowdfundingmentioning
confidence: 99%
“…People are satisfied by contributing to projects that make an impact, have social merit, and generate macro-economic implications in terms of income redistribution (Grüner and Siemroth, 2019). In this sense, we argue that the pledgers disregard self-benefit and prefer social benefits, contributing to higher rates for social projects, rather than other project types such as art, and they do so even more intensively in cities with higher income inequalities.…”
Section: Introductionmentioning
confidence: 81%
“…They provide evidence that financial inclusion is a key channel through which FinTechs reduce income inequality. Grüner and Siemroth (2019) have shown that decentralized individual investments can efficiently allocate capital to innovating firms via crowdfunding. Furthermore, Kimura et al (2018) have argued that a local disparity in income distribution can encourage pledgers to donate money.…”
Section: H3mentioning
confidence: 99%